2014
DOI: 10.1080/17518253.2014.944941
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel graphene-like layered hexagonal boron nitride for adsorptive removal of antibiotic gatifloxacin from aqueous solution

Abstract: (2014) Development of novel graphene-like layered hexagonal boron nitride for adsorptive removal of antibiotic gatifloxacin from aqueous solution, Green Chemistry Letters and Reviews, 7:4, 330-336, DOI: 10.1080/17518253.2014 Graphene-like layered hexagonal boron nitride (g-BN) was prepared and characterized. The performance of using g-BN as an adsorbent for removal of fluoroquinolone antibiotic gatifloxacin (GTF) from aqueous solution was evaluated. g-BN showed an excellent adsorption capability with notable G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…And the adsorbate (gatifloxacin) has two aromatic rings, which can serve as a π-electron donor. 12 Besides, Xiong et al suggested that Lewis acid–base interaction plays an important role in removing aromatic sulfocompounds from fuels. 8 In addition, the mechanism of adsorption of aromatic sulfocompounds is suggested to be π-complexation on other adsorbents, such as Ag-Y and Cu-Y zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…And the adsorbate (gatifloxacin) has two aromatic rings, which can serve as a π-electron donor. 12 Besides, Xiong et al suggested that Lewis acid–base interaction plays an important role in removing aromatic sulfocompounds from fuels. 8 In addition, the mechanism of adsorption of aromatic sulfocompounds is suggested to be π-complexation on other adsorbents, such as Ag-Y and Cu-Y zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was observed that the structural formulas of methylene blue and tetracycline showed no strong bonds with chlorine, showing Lewis basicity. Therefore, a portion of the adsorption driving force may come from the interactions with Lewis acids of sea urchin‐like h‐BN to form the acid‐base complexation 43 . Meanwhile, the introduction of carbon in h‐BN may effectively increase the molecular orbital energy level and reduce the chemical hardness, thereby improving the adsorption capacity of sea urchin‐like h‐BN adsorbents (lower hardness means higher adsorption capacity 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a portion of the adsorption driving force may come from the interactions with Lewis acids of sea urchin-like h-BN to form the acid-base complexation. 43 Meanwhile, the introduction of carbon in h-BN may effectively increase the molecular orbital energy level and reduce the chemical hardness, thereby improving the adsorption capacity of sea urchin-like h-BN adsorbents (lower hardness means higher adsorption capacity 31 ). Also, the defects formed by the staggered h-BN layered structure are also beneficial to the improved h-BN adsorption capacity.…”
Section: F I G U R Ementioning
confidence: 99%
“…Among these methods, adsorption has been considered as an economic, effective, and attractive technology due to its non‐destructive feature and simple operation . By now, a great number of adsorbents, such as activated carbons , multi‐walled carbon nanotubes , graphene oxide , mesoporous silica , polymer resins , biomass ashes , clay minerals , and graphene‐like boron nitride have been evaluated for tetracycline removal. To date, the development of new adsorbent for removal of the tetracycline is still highly desired.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the development of new adsorbent for removal of the tetracycline is still highly desired. The findings in our previous work demonstrated that graphene‐analogue layered inorganic materials had an excellent potential as adsorbents in the removal of doxycycline and gatifloxacin from aqueous solution and showed high adsorption capacity . Graphene‐analogue layered molybdenum disulfide (G‐MoS 2 ) is a novel material similar to graphene.…”
Section: Introductionmentioning
confidence: 99%